(untitled) (Bangladesh Journal of Agricultural Research, 2019)
The experiment was undertaken to develop the processing method for sweetened condensed milk from corn to enhance the diversified use of corn. After extracting the milk from milky/dough stage corn (after 5 to 6 weeks of sowing), it was processed into condensed milk. The sweetened condensed corn milk prepared from the combination of 80% sugar of total extracted milk with carboxymethyl cellulose (CMC) at 0.3% of milk obtained the highest acceptability rank (8.67, "like very much" to "like extremely") after 8 weeks of storage at ambient condition. The minimum microbial load was observed in the combination of 85% sugar and 0.3% CMC of corn milk which followed by 80% sugar and 0.3% CMC of corn milk combination during storage. The retention of vitamin C (5.88 mg/100g) and vitamin A (ß- carotene, 6.98 μg/100g) was found better in the condensed corn milk prepared with the combination with 80% sugar and 0.3% CMC of corn milk after 8 weeks. Bangladesh J. Agril. Res. 44(2): 377-385, June 2019